MUKALLAF SEBAGAI SUBJEK HUKUM DALAM FIQIH JINAYAH - Abdur Rakib (JURNAL HAKAM, 2021)
Legal actors in the study of jinayah fiqh are an important part in the further study of jinayah fiqh, as are legal actors in muamalah fiqh, worship, and munakahat which of course cannot be separated from the discussion of mukallaf as the perpetrator of the legal discussion in it, where every law is certain because there are legal actors, or where there are humans (mukallaf) there must be laws resulting from their actions. The importance of the study of mukallaf in this more specific discussion is of course because the perpetrators or legal subjects – if not call it mukallaf – in the context of jinayah fiqh there are some differences in the imposition of taklif when compared to the fiqh of Mawarits, even with the fiqh of worship. Mukallaf in the discussion of jinayah fiqh basically has no difference with other fiqh except in the discussion of the expertyah category wujub al-kamilah. In essence, fiqh is God's law which is based on the absence of burdens on His servants who are beyond the limits of ability.